PERKEMBANGAN PEMBANGUNAN HUTAN TANAMAN RAKYAT DI PROVINSI NUSA TENGGARA BARAT DAN ESTIMASI HARGA KAYUNYA - Subarudi Subarudi (Pusat Penelitian dan Pengembangan Sosial, Ekonomi, Kebijakan dan Perubahan Iklim, 2014)
Community plantation forest (CPF) has not well developed nationally. The objectives of the study are: 1) to explain the development of CPF inWest Nusa Tenggara Province, 2) to estimate CPF wood price in NTB and 3) to compare the estimation results for finding the right wood price estimation. The results of study indicated that this province has obtained the utilization business permit of CPF with area of 4,396 ha and has been realized around 1,665.81 ha or 38%. The price calculation of sengon (Paraserianthes falcaria) using methods of stumpage price, market price and social price respectively found: 1) stumpage price of IDR 164,593 per m , 2) market price of IDR 400,000 per m and 3) social price/parity of IDR 275,000 per m . Its price range can be used as basic price offering from CPF farmer.Nevertheles, the estimation method of CPF wood price derived from the modified price determination of fresh fruit bunches of palm oil is more oriented to win-win solutions for both sellers and buyers.